Advanced computing, networking and informatics. proceedings of the 3rd International Conference on Advanced Computing, Networking, and Informatics (ICACNI 2015) /: proceedings of the 3rd International Conference on Advanced Computing, Networking, and Informatics (ICACNI 2015). Volume 2 : ([2016]) - Unknown
No abstract available